2015
DOI: 10.1007/s00464-015-4214-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open liver resection for hepatocellular carcinoma in posterosuperior segments

Abstract: LLR for selected patients with HCC in the posterosuperior segments may offer the same oncologic outcomes as conventional procedures, while being associated with such advantages as lower blood loss, fewer postoperative complications, and shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 24 publications
1
39
0
2
Order By: Relevance
“…Through the preliminary search, 990 articles are obtained. After reading titles and abstracts and full texts and removing duplicate documents, 47 articles were included in our study, which involved 5889 patients (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Through the preliminary search, 990 articles are obtained. After reading titles and abstracts and full texts and removing duplicate documents, 47 articles were included in our study, which involved 5889 patients (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The evidence indicates that LLR is safe when performed by surgeons with sufficient experience. In addition, laparoscopic segmentectomy may be suitable for cases involving technically challenging posterosuperior segments and segment I, if surgeons improve their skills and exercise ingenuity 26, 88, 89…”
Section: Indications and Oncological Outcomesmentioning
confidence: 99%
“…Laparoscopic hepatectomy was performed according to the Chinese expert consensus on laparoscopic hepatectomy and the relevant surgical guidelines. A detailed description of patient positioning and trocar locations has been reported previously. Intraoperative ultrasonography (Toshiba, Hitachi, Tokyo, Japan) was used to identify the location and size of the tumour, its relationships with the major intrahepatic ducts, the location of main intrahepatic ducts on the liver parenchymal transection plane, and to search for any metastatic site in other parts of the liver or tumour thrombus in the portal vein and/or hepatic vein.…”
Section: Methodsmentioning
confidence: 99%
“…Tumour size and location are two important factors in determining the indications for laparoscopic hepatectomy in patients with HCC. Some studies have shown that laparoscopic hepatectomy can be undertaken in patients with HCC located in the posterosuperior liver segments (segments I, IVa, VII and VIII). However, whether a large tumour size is a contraindication to laparoscopic hepatectomy remains controversial.…”
Section: Introductionmentioning
confidence: 99%